Comparison of in-hospital and out-of-hospital cardiac arrest patients receiving targeted temperature management: A matched case-control study. Issue 9 (5th May 2020) - Chen, Chung-Ting; Chen, Cheng-Han; Chen, Tzu-Yin; Yen, David Hung-Tsang; How, Chorng-Kuang; Hou, Peter Chuanyi
Abstract : Background: Evidences that support the use of targeted temperature management (TTM) for in-hospital cardiac arrest (IHCA) are lacking. We aimed to investigate the hypothesis that TTM benefits for patients with IHCA are similar to those with out-of-hospital cardiac arrest (OHCA) and to determine the independent predictors of resuscitation outcomes in patients with cardiac arrest receiving subsequent TTM. Methods: This is a retrospective, matched, case-control study (ratio 1:1) including 93 patients with IHCA treated with TTM after the return of spontaneous circulation, who were admitted to Partners HealthCare system in Boston from January 2011 to December 2018. Controls were defined as the same number of patients with OHCA, matched for age, Charlson score, and sex. Survival and neurological outcomes upon discharge were the primary outcome measures. Results: Patients with IHCA were more likely to have experienced a witnessed arrest and receive bystander cardiopulmonary resuscitation, a larger total dosage of epinephrine, and extracorporeal membrane oxygenation. The time duration for ROSC was shorter in patients with IHCA than in those with OHCA. The IHCA group was more likely associated with mild thrombocytopenia during TTM than the OHCA group. Survival after discharge and favorable neurological outcomes did not differ between the two groups. Among all patients who had cardiac arrest treated with TTM, the initial shockable rhythm, time to ROSC, and medical history of heart failure were independent outcome predictors for survival to hospital discharge. The only factor to predict favorable neurological outcomes at discharge was initial shockable rhythm. Conclusion: The beneficial effects of TTM in eligible patients with IHCA were similar with those with OHCA. Initial shockable rhythm was the only independent predictor of both survival and favorable neurological outcomes at discharge in all cardiac arrest survivors receiving TTM.